Human papillomavirus prevalence and vaccine effectiveness in young women in Germany, 2017/2018: results from a nationwide study - Loenenbach, Anna; Schönfeld, Viktoria; Takla, Anja; Wiese-Posselt, Miriam; Marquis, Adine; Thies, Sarah; Sand, Matthias; Kaufmann, Andreas M.; Wichmann, Ole; Harder, Thomas (Frontiers in Public Health, 2023)
Background: Infections with Human Papillomaviruses (HPV) are sexually transmitted and can cause cancer. In Germany, vaccination against HPV is recommended for girls and boys aged 9-17 years. We aimed to investigate HPV DNA prevalence, genotype distribution and vaccine effectiveness (VE) in women aged 20-25 years ten years after the introduction of HPV vaccination in Germany (2018)(2019), and compared these data to an equally designed study from 2010-2012.Methods: 76 geographical clusters were randomly selected, followed by random selection of 61 women aged 20-25 years per cluster. Participants performed cervicovaginal self-sampling and answered questions on demographics, sexual behaviour and HPV vaccination. Samples were tested for 18 high risk and nine low risk HPV genotypes. We performed chi-square tests, Fisher's exact test, unpaired Student's t-test and proportion t-test, and calculated crude and adjusted prevalence ratios (PR) and 95% CIs.Results: Of 7,858 contacted women a total of 1,226 agreed to participate. Of these, 94 women were positive for HPV types 16 and/or 18. HPV16 prevalence was 7.0% (95%CI 5.6-8.6) and HPV18 prevalence was 0.8% (95%CI 0.4-1.5). HPV6 and HPV11 were rare with only five (0.4%; 0.1-0.9) and one (0%; 95%CI 0.0-0.5) positive tests. 757 women (62%) had received at least one HPV vaccine dose and 348 (28%) were vaccinated as currently recommended. Confounder-adjusted VE was 46.4% (95%CI 4.2-70.1) against HPV16/18 infection and 49.1% (95%CI 8.2-71.8) against infection with at least one HPV genotype covered by the quadrivalent HPV vaccine. Compared with the 2010-2012 study results, HPV16/18 prevalence dropped from 22.5% (95%CI 19.0-26.3) to 10.3% (95%CI 7.5-13.9; p<0.0001) in unvaccinated participants.Vaccine-covered HPV genotypes were rare among 20-25-year old women in Germany and decreased compared to the time point shortly after the start of the HPV vaccination program.HPV prevalence of almost all vaccine-covered genotypes was strongly reduced in vaccinated participants. A decrease of HPV16 and HPV18 was even observed in unvaccinated participants, compared to 2010-2012 data, suggesting indirect protection of unvaccinated women. Low VE against HPV16/18 and HPV6/11/16/18 in our study might be attributable to study design in combination with the endpoint selection of (mainly transient) HPV DNA positivity.